THE RELATIONSHIP BETWEEN DEMOGRAPHIC FACTORS TOWARDS FINANCIAL LITERACY AND FINANCIAL INCLUSION AMONG FINANCIALY EDUCATED STUDENT IN INSTITUT TEKNOLOGI BANDUNG - Nevi Febriana, Rachel
The global financial crisis provoked countries until individuals to be more aware of the financial knowledge. Many improvements have taken place in Indonesia following the financial crisis. But as the economic getting stronger, Indonesia now facing the emerging challenge known as ASEAN Economic Community Era. As AEC offers many great opportunities, it also demands people to be more competitive, financially literate and encourage financial inclusiveness. Young people as the future of a nation are up to this challenge. Furthermore, Indonesia financial literacy and financial inclusion are still categorized as low even among the students/ Aware of this situation, this research aim to analyze student, particulary in Institut Teknologi Bandung, financial literacy and inclusion level and its determinant. ITB known as one of the best public university in the nation and was famous with its good track record. Since the presence of School of Business and Management, ITB is now equipped with financial- related courses to help student understand about financial matters. Thus, the author wants to investigate ITB student who already took financial-related course. This study found out that although the student have already got financial-related course, their advanced financial literacy is still low, while basic financial literacy is now in the low-to-medium level. Financial inclusion index is around 74% shows that ITB student has already exposed by financial product and services. Furthermore, using multi linear regression, the research found out that age and education are two important determinants to accelerate student financial literacy, while to be financially inclusive, the determinants are age, education and head of family’ occupation. This is a unique finding to help government and academic institution to create strategies to increase student financial literacy and inclusion. In the end, the author also provides the study with feasible recommendations which is to develop a practical-based course, encouraging financial education as a mandatory course across all major to be taught as early as possible, and recommending futher research to expand the respondent and investigated other factors than demographic.